Government support measures as a factor in managing the digitalization of small and medium-sized enterprises in agriculture - Sheina Ekaterina; Skvortsov Egor; Lylov Anton; Pryadilina Natalya (BIO Web of Conferences)
The targeting and timeliness of financial and non-financial measures of state support for small and medium-sized enterprises in the field of agriculture within the framework of ongoing state support for entrepreneurship in the Russian Federation are currently crucial not only for a specific industry, but also for the national economy of the country as a whole, as they minimize the risks associated with the specifics of the activities of these enterprises, and make it possible to redistribute the resources released as a result of the support received to enhance the digitalization of business processes. The authors investigated the results of providing financial and non–financial support to SMEs in the Sverdlovsk region, including in the field of agriculture, received from the regional Development Institute of the Sverdlovsk region for the period from 2021 to 2023. The conclusions obtained by the authors showed the need to strengthen measures to support small and medium-sized enterprises in the field of agriculture by the state through regional development institutions, which will ensure the growth and scaling of their business and allow for a more comprehensive implementation of digitalization processes in business planning and operational management of enterprises.